Diurnal and seasonal variation of Pasquill stability classes at a coastal station - SADHURAM, Y; VITTALMURTHY, KPR (MAUSAM, 1986)
Atmospheric stability is one of the most important and useful meteorological parameter in air pollution studies. There are several indicators to determine the stability of the atmosphere. In this article the authors have computed stabilities according to Pasquill for a coastal station, viz., Visakhapatnam using a 10-year data ( 1958-67). The study reveals that unstable conditions during night time and stable conditions during day time are not observed in all the four months, viz., January, April, August and October typical of the respective seasons, Neutral condition is present at day and night with high percentage frequencies at the time of just after sunrise and before sunset. The study of stability wind roses indicate that highly and moderately unstable conditions and stable conditions are associated with low wind speeds and slightly unstable and neutral conditions are associated with high wind speeds.